PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN KONSENTRASI DAN KECERDASAN LOGIS MATEMATIS - Tirta; Buyung (DIADIK, 2022)
The purpose of this study was to describe the application of the demonstration method to improve concentration and mathematical intelligence of early childhood logistics group B RA Al-Ikhlas Kandang Limun, Bengkulu City. This study used Classroom Action Research (CAR) which was carried out in 3 cycles and continued with a quasi-experimental class with a sample population of 11 children. The subjects of this study were group B children in RA Al-Ikhlas Kandang Limun, Bengkulu City, totaling 11 children. The data collection technique used a child's observation sheet about concentration and logical-mathematical intelligence. Data analysis used research mean (mean) and t-test. The results of the study prove that through the application of the demonstration method can significantly increase the concentration and logical mathematical intelligence of children in cycles 1, 2, and 3. Thus the application of the appropriate demonstration method is used for concentration and logical mathematical intelligence of children and becomes the right alternative for learning